PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN PADA TIM FUTSAL SMA NEGERI 5 SIJUNJUNG (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effect of interval training on endurance in the Futsal team at SMA Negeri 5 Sijunjung. This study used a one group pretest-postest design approach. In the design there is a pretest, before being given treatment. Thus the results of treatment can be known to be more accurate, because it can be compared with the conditions before being treated and after being given treatment. After that, the Posttest Balke was carried out, the data obtained were analyzed descriptively, then the research hypothesis was tested according to the problem, namely: